2021
DOI: 10.1103/physrevapplied.16.024005
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Prediction of Megapixel Longitudinal Phase-Space Images of Electron Beams Using Encoder-Decoder Neural Networks

Abstract: Modeling of large-scale research facilities is extremely challenging due to complex physical processes and engineering problems. Here, we adopt a data-driven approach to model the longitudinal phase-spacediagnostic beamline at the photoinector of the European XFEL with an encoder-decoder neural-network model. A deep convolutional neural network (decoder) is used to build images, measured on the screen, from a small feature map generated by another neural network (encoder). We demonstrate that the model, traine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The latest work at the European XFEL injector demonstrated that a deep encoder-decoder neural network can achieve extremely high accuracy in predicting megapixel LPS images using up to three RF phases as input. The current profile, energy spectrum and slice energy spread extracted from the predicted LPS image all show very good agreement with the measurement [18]. In addition, an innovative method was demonstrated to efficiently build large models with multiple distinctive work-FIG.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…The latest work at the European XFEL injector demonstrated that a deep encoder-decoder neural network can achieve extremely high accuracy in predicting megapixel LPS images using up to three RF phases as input. The current profile, energy spectrum and slice energy spread extracted from the predicted LPS image all show very good agreement with the measurement [18]. In addition, an innovative method was demonstrated to efficiently build large models with multiple distinctive work-FIG.…”
Section: Introductionsupporting
confidence: 52%
“…During the first 400 epochs, both L LP S and L spectrum are the mean squared error (MSE) and w is set to 1. During the second 400 epochs, L LP S is changed to the multiscale structural similarity index measure (SSIM) [37] with hyperparameters defined in [18] and w is set to 100 empirically in order to make the losses of the two decoders at the same order of magnitude at the end of the training. There are two advantages for using different loss functions for the LPS image decoder in different training phases.…”
Section: B Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, machine learning has demonstrated to be able to learn relationships inside a complex system and produce accurate and fast predictions [12,13]. Using artificial neural networks as a tool for electron bunch longitudinal property prediction has garnered more and more attention in recent years [14][15][16][17][18]. At the LCLS, early work has demonstrated prediction of LPS images and current profiles at the linac exit using two separated multi-layer perceptrons (MLPs) [14] and a single input parameter.…”
Section: Introductionmentioning
confidence: 99%